Red meat and different dietary patterns and cardiovascular health - the review - Borowiecka, Monika; Góralczyk, Wanesa; Zając, Marlena; Brzezińska, Agnieszka (Journal of Education, Health and Sport, 2021)
Introduction: Cardiovascular diseases are in a majority of health issues worldwide. Dietary habits have been extensively studied in the cardiovascular area since they are responsible for improvement or deterioration of that system condition. One of the most commonly mentioned product is red meat, both processed and unprocessed. Brief description of the state of knowledge: The aim of this review was to present currently available knowledge in the online database PubMed about consumption of red meat and cardiovascular health. The article covers scientific papers which indicate to the risk factor, which is intake of processed and unprocessed meat, and eventually incidents of CVD. It is also claimed that effects of consumption that group of protein may be dependent of its dosage. Conclusions: The review support an assumption that dietary patterns, in this case red meat, processed and unprocessed, play a significant role in being CVD risk factors. Besides, that influence should be measured more precisely and new scientific tools for tracking dietary habits should be input.